2016
DOI: 10.1111/maps.12732
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and irradiation history of lunar meteorite Dhofar 280

Abstract: Dhofar 280 recorded a complex history on the Moon revealed by high‐resolution 40Ar‐39Ar dating. Thermal resetting occurred less than 1 Ga ago, and the rock was exposed to several impact events before and afterwards. The cosmic ray exposure (CRE) age spectrum indicates a 400 ± 40 Ma CRE on the lunar surface. A unique feature of this lunar sample is a partial loss of cosmogenic 38Ar, resulting in a (low‐temperature) CRE age plateau of about 1 Ma. This was likely caused by the same recent impact event that reset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…Two whole rock (WR) samples (Dhofar 1436-a and Dhofar 1436-b) weighing 25.8 and 31.1 mg were used for 40 Ar- 39 Ar dating. Our previous study of the meteorite Dhofar 280 (Korochantseva et al 2016) has demonstrated that significant chronological and geochemical information could be obtained by analyzing a WR chip of the Dhofar 280 lunar impact melt breccia. The sample Dhofar 1436-b contained a higher proportion of clastic material than Dhofar 1436-a.…”
Section: Sample Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two whole rock (WR) samples (Dhofar 1436-a and Dhofar 1436-b) weighing 25.8 and 31.1 mg were used for 40 Ar- 39 Ar dating. Our previous study of the meteorite Dhofar 280 (Korochantseva et al 2016) has demonstrated that significant chronological and geochemical information could be obtained by analyzing a WR chip of the Dhofar 280 lunar impact melt breccia. The sample Dhofar 1436-b contained a higher proportion of clastic material than Dhofar 1436-a.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…Ozima et al (2004) noted quantitative problems with the origin of the orphan argon according to the "antiquity" scenario. There are data (Fernandes et al 2000(Fernandes et al , 2003Cohen et al 2005b;Korochantseva et al 2016) inconsistent with the empirical antiquity model (Eugster et al 2001), raising the issue about a simple relation between age and the trapped 40 Ar/ 36 Ar ratio in lunar samples.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations